22. STRUCTURAL AND SPECTROSCOPIC MRI CHARACTERISTICS OF THE BRAIN IN ELDERLY WITH MILD COGNITIVE IMPAIRMENT (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to compare brain magnetic resonance imaging characteristics between patients with mild cognitive impairment and normal cognitive.Subjects and methods: The study was conducted on 40 elderly patients with mild cognitive impairment and 40 control patients without cognitive impairment at National Geriatric Hospital from July 2024 to April 2025. Evaluated parameters included: the degree of cortical atrophy in specific brain regions, bilateral hippocampal volumes, and neurochemical ratios such as NAA/Cr, mI/Cr, NAA/mI, and Cho/Cr using structural magnetic resonance imaging and magnetic resonance spectroscopy.Results: Magnetic resonance imaging findings revealed significantly greater global brain atrophy, as well as atrophy in the temporal and parietal lobes, and reduced hippocampal volumes in the mild cognitive impairment group compared to the control group (p < 0.001). Spectroscopy results showed significantly decreased NAA/Cr and NAA/mI ratios, along with an increased mI/Cr ratio in the mild cognitive impairment group (p < 0.01), indicating neuronal degeneration and increased glial activation. The mI/Cr ratio demonstrated potential in distinguishing mild cognitive impairment from normal aging, with a sensitivity of 75% and specificity of 60% at a cutoff value > 0.615.Conclusion: Structural magnetic resonance imaging and magnetic resonance spectroscopy indices show promise as potential biomarkers for early diagnosis and differentiation of mild cognitive impairment from normal aging.
Keywords: Mild cognitive impairment; structura magnetic resonance imaging; magnetic resonance spectroscopy